Na lei do jogo está tudo dito: os jogos gauchescos e a modernidade na Região Platina (1852-1901) - Costa, Matheus Donay da (2025)
The present dissertation focuses on the study of leisure activities in the rural areas of the Prata Region, through what we term "gaucho games," and the limits imposed by the economic and political modernization of the region during the second half of the nineteenth century. We consider gaucho games to be those associated with rural culture that became part of the social imaginary of the gaucho and criollo populations in the region, such as truco card games, the bone/tava game, and horse races. In this work, we draw on sources of various types, including periodicals, state reports, literary texts, essays, legal jurisdictions, and criminal cases. Initially, we present the characteristics of these games and analyze their occurrence in the borderlands, understood transversally across the territories of Rio Grande do Sul, Uruguay, and Argentina. We also aim to understand the main reasons that led these games and their players to occupy a marginalized position in the rural environment during the second half of the 19th century. Finally, we examine how discussions regarding these leisure activities are supported by the analysis of game-related situations described in criminal cases. We find that the repressive measures against popular entertainments were part of a broader context of economic rationality and state modernization in Hispanic countries, particularly through laws targeting the idle and disorderly and the establishment of rural codes. These strategies present notable differences when compared to the Brazilian state's approach, but they by no means signified the absence of control over the popular classes' leisure time.